Low serum vitamin D levels are associated with a low percentage of TREM-2+ monocytes in low-grade gliomas and poorer overall survival in patients with high-grade gliomas - Klučková, Kristína; Kozák, Ján; Szaboová, K; Suchánková, Magda; Švajdler, Marián; Blažíčková, Stanislava; Makohusová, Miroslava; Šteňo, Juraj; Matejčík, Viktor; Bucová, Mária (Bratislavské lekárske listy, 2021)
INTRODUCTION: Anti-inflammatory effect of vitamin D (VD) could be beneficial in improving the survival of glioma patients. The aim of our study was to analyse the serum levels of vitamin D in glioma patients and to find an association with the prognosis of glioma patients and other investigated parameters. MATERIAL AND METHODS: The study included 63 patients with gliomas. Percentage of CD14+ monocytes, TREM-1+ and TREM-2+ monocytes were determined by flow cytometry, serum levels of 25(OH)D were evaluated by electrochemiluminescent binding test. RESULTS: Six patients out of 63 had normal levels of VD. A significant difference in the overall survival (OS) in the patients with severe VD deficiency, VD deficiency and insufficiency in grade IV was found. In grade II and III, the levels of vitamin D positively correlated with the percentage of TREM-2+ monocytes, and in grade II also a negative correlation of VD with TREM-1/TREM-2 ratio was observed. CONCLUSION: Levels of VD could influence the prognosis of patients with high-grade gliomas. Serum level of 25(OH)D in low-grade gliomas positively correlated with the percentage of anti-inflammatory acting TREM-2+ monocytes and negatively with TREM-1/TREM-2 ratio. This could be protective against the progression to high-grade glioma, because TREM-2 is associated with protective functions such as: tissue repair, control of local inflammation, or phagocytosis (Tab. 4, Fig. 4, Ref. 79).
Keywords: dospělí; Kaplan-Meier Estimate; gliom; Female; Adult; ženské pohlaví; Kaplanův-Meierův odhad; lidé; Survival Analysis; vitamin D; monocyty; Glioma; prognóza; Vitamin D; Monocytes; Male; Aged; Prognosis; analýza přežití; lidé středního věku; senioři; mužské pohlaví; TREM2; Middle Aged; Humans